Time as Dimension or Illusion? A Critical Analysis within the Framework of Relativity - Praveen Sah; Neha Shah; Dilip Kumar Sah; Suresh Kumar Sahani (Darul Yasin Al Sys, 2026)
The nature of time remains a central problem in both physics and philosophy, particularly in light of the tension between classical and relativistic conceptions of temporality. This paper examines the question of whether time is an illusion within the framework of relativity. Whereas classical physics treats time as absolute, universal, and uniformly flowing, Einstein’s theory of relativity demonstrates that temporal intervals vary according to relative motion and gravitational fields. Building on this framework, the paper argues that time is operationally real insofar as it can be measured and modeled physically, yet the notion of a universally shared and continuously flowing present has no firm basis in modern physics. The analysis further suggests that the relativistic view of spacetime supports the coexistence of past, present, and future within a unified four-dimensional structure. It also considers whether the human experience of temporal passage arises from fundamental physical laws or from cognitive and thermodynamic asymmetries. The paper concludes that time itself is not an illusion; rather, what is misleading is the classical intuition that time flows identically for all observers. This study contributes to ongoing interdisciplinary debates by clarifying how relativity reshapes the philosophical interpretation of temporal reality.